Analisis Efisiensi Teknis Penggunaan Pupuk dan Pestisida Budidaya Asparagus di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - SIDHARTA, NUR RANGGA; SUDARMA, I MADE; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017)DO - 10.24843/JAA.2017.v06.i01.p17, 2017)
Analysis of Technical Efficient Use of Fertilizer and Pesticide Cultivation Asparagus di Desa Pelaga, Kecamatan Petang, Kabupaten Badung Pelaga Village located at the Subdistrict of Petang, Badung Regency is an area thatcarry out the program of One Village One Product (OVOP) with asparagusdistinctive product since 2010. Cultivation of asparagus is influenced by the use offertilizers and pesticides including chicken manure, cow manure, urea, NPK andpesticides, where the quantity of fertilizer and pesticide use affects the production ofasparagus. This research aimed to analyze the effects of the use of fertilizers andpesticides, the farmer acceptance and to analyze the technical efficiency ofcultivation of asparagus.This research uses multiple linear regression method thatincludes: classic assumption test consisting of normality test, heteroscedasticity, testof multicoliniearity and test the linear regression model, which includes: coefficienttest determination (R2), F-test and t-test with a level real (?) of 5%. After that, inorder to analyze the technical efficiency by using the Data of Envelopment Analysis(DEA). The equation used is the production function model of Cobb-Douglasproduction function of the natural logarithm.The use of fertilizers and pesticidestogether in the cultivation of asparagus significantly affected the production ofasparagus. Partially only cow manure (X2) and NPK (X4) which significantlyaffected the production of asparagus, asparagus farmers’ income was Rp. 3,219,932for a month and already exceeds the Minimum Wage of Badung Regency. Based onthe analysis of technical efficiency, the asparagus cultivation has been efficient buthas not been able to achieve performance levels of efficiency of full-technicallyefficient, because the average technical efficiency achieved was 63%, with a rangebetween 38.5% and 100%. The value of technical inefficiency or technicallyinefficient average is 37%.
Keywords: asparagus, efficiency, fertilizers, pesticides, production